Ten-Year Risk Factors for Inferior Knee Injury and Osteoarthritis Outcome Score After Anterior Cruciate Ligament Reconstruction: A Study of 874 Patients From the Swedish National Knee Ligament Register. Issue 12 (October 2018) - Hamrin Senorski, Eric; Svantesson, Eleonor; Spindler, Kurt P.; Alentorn-Geli, Eduard; Sundemo, David; Westin, Olaf; Karlsson, Jon; Samuelsson, Kristian
Background: Factors relating to the patient and anterior cruciate ligament (ACL) reconstruction may help to identify prognostic factors of long-term outcome after reconstruction. Purpose: To determine 10-year risk factors for inferior knee function after ACL reconstruction. Study Design: Cohort study; Level of evidence, 2. Methods: Prospectively collected data from the Swedish National Knee Ligament Register were extracted for patients who underwent ACL reconstruction between January 2005 and December 2006. Patients who had no data at the 10-year follow-up for the Knee injury and Osteoarthritis Outcome Score (KOOS) were excluded. Multivariable proportional odds regression modeling was used to assess 10-year patient- and surgery-related risk factors across all the KOOS subscales and the KOOS4 (mean score of 4 subscales: pain, knee-related symptoms, function in sport and recreation, and knee-related quality of life). Results: A total of 874 (41%) patients were included (male, 51.5%; median age at the time of ACL reconstruction, 27.5 years [range, 11.2-61.5 years]). An increase in the severity of concomitant articular cartilage injuries resulted in a reduced KOOS on 4 subscales (odds ratio, 0.64-0.80; P < .05). A higher preoperative KOOS pain score increased the odds of a higher score on the pain, symptoms, and sport subscales and the KOOS4 . In addition, a higher preoperative body mass index was a significant risk factor for lower scores on 3 KOOS subscales and the KOOS4 . No patient- or surgery-related predictor was significant across all KOOS subscales. Conclusion: This 10-year risk factor analysis identified several factors that can affect long-term knee function after ACL reconstruction. Most risk factors were related to preoperative patient-reported outcome and potentially modifiable. On the other hand, most of the surgery-related risk factors were nonmodifiable. Nevertheless, this information may be helpful to physicians and physical therapists counseling patients on their expectations of outcome after ACL reconstruction.